2021
DOI: 10.3390/ph14121245
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of a Selective Antibiofilm Peptide SK-24 Derived from the NMR Structure of Human Cathelicidin LL-37

Abstract: The deployment of the innate immune system in humans is essential to protect us from infection. Human cathelicidin LL-37 is a linear host defense peptide with both antimicrobial and immune modulatory properties. Despite years of studies of numerous peptides, SK-24, corresponding to the long hydrophobic domain (residues 9–32) in the anionic lipid-bound NMR structure of LL-37, has not been investigated. This study reports the structure and activity of SK-24. Interestingly, SK-24 is entirely helical (~100%) in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These two peptides also displayed similar hemolysis with comparable 50% hemolytic concentrations (HC 50 ). 37 Taken together, these results underscore comparable antimicrobial and hemolytic ability of GF-17 and 17BIPHE2, making them an ideal peptide pair for us to compare their antibiofilm capabilities in vitro and in vivo as well. Our study underscores that this requirement is determined by both the peptide concentration and the initial CFU in the culture.…”
Section: ■ Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These two peptides also displayed similar hemolysis with comparable 50% hemolytic concentrations (HC 50 ). 37 Taken together, these results underscore comparable antimicrobial and hemolytic ability of GF-17 and 17BIPHE2, making them an ideal peptide pair for us to compare their antibiofilm capabilities in vitro and in vivo as well. Our study underscores that this requirement is determined by both the peptide concentration and the initial CFU in the culture.…”
Section: ■ Discussionmentioning
confidence: 59%
“…However, peptide stability did not show a clear advantage in numerous in vitro experiments, including antimicrobial susceptibility assays (Tables and and S1), killing kinetics, and membrane permeabilization studies (Figure ). These two peptides also displayed similar hemolysis with comparable 50% hemolytic concentrations (HC 50 ) . Taken together, these results underscore comparable antimicrobial and hemolytic ability of GF-17 and 17BIPHE2, making them an ideal peptide pair for us to compare their antibiofilm capabilities in vitro and in vivo as well.…”
Section: Discussionmentioning
confidence: 64%
“…D-LL-37, an LL-37 derivative in which all amino acids are changed to the D-form, displayed protease-resistance properties while possessing biofilm-inhibition capacity equal to the L-peptide isomer LL-37 (inhibiting ~40% biofilm formation at a concentration of 10 μg/ml) and immunostimulatory activity and wound-healing properties on the host higher than the L-peptide ( Dean et al, 2011 ). SK-24, which corresponds to residues 9–32 of LL-37, demonstrated killing activity against S. aureus and Staphylococcal biofilm reduction, which was superior to LL-37 and several other derivatives ( Zhang et al, 2021 ). KE-18, a derivative corresponding to residues 15–32 of LL-37, showed significant biofilm prevention against S. aureus ( Luo et al, 2017 ).…”
Section: Human Amps That Have Antibacterial Activity Against Staphylo...mentioning
confidence: 98%
“…The two helices are separated by a bend or break. Furthermore, it has been found that the discontinuation is found on the hydrophobic surface at S9, rather than the helix ( Figures 2B,C ) ( Wang, 2008 ; Zhang et al, 2021 ).…”
Section: Characteristics and Structure Of Ll-37mentioning
confidence: 99%